Mengkaji Perilaku Seks Daring Dari Perspektif Hukum Taurat - Natallia Natallia; Sandra Rosiana Tapilaha (Jurnal Ilmu Teologi dan Pendidikan Agama Kristen, 2023)
Penelitian ini membahas relevansi hukum Taurat sebagai nilai moral bagi remaja Kristen menghadapi penyimpangan seks daring di zaman digital. Hukum Taurat dapat memberikan remaja memahami peran dan tujuan hidupnya sebagai orang percaya. Penelitian ini menyatakan bahwa nilai moral dalam hukum Taurat tetap relevan dan harus dipelihara sebagai bagian dari moralitas remaja Kristen. Penelitian ini juga menjelaskan bagaimana pendidik Kristen dapat mengajarkan hukum Taurat yang relevan dengan zaman teknologi dan digital dalam menangani masalah seks daring. AbstractThis study discusses the relevance of the Torah law as a moral value for Christian teenagers in facing the issue of online sexual deviance like cybersex. The discussion is conducted by examining the Torah law in both the Old and New Testaments and highlighting the importance of remembering the Torah teachings in guiding teenagers to face the moral challenges of the digital age. The study explains that the moral values contained in the Torah law can help teenagers understand their roles and purposes as believers in the digital age. The study argues that the Torah law remains relevant and must be upheld as part of the moral values of Christian teenagers. The researchers acknowledge that everything in the Holy Scripture has value and power, and that we must believe and obey its commandments. This study aims to produce a description of how Christian educators can teach relevant Torah law to address the issue of cybersex in the digital age.